# How do you use the Product Rule to find the derivative of #y = x(x^2 - 2)^(3/2)#?

##### 1 Answer

#### Answer:

#### Explanation:

Your function can be written as the product of two other functions

#y = underbrace(x)_(color(orange)(f(x))) * underbrace((x^2-2)^(3/2))_(color(red)(g(x)))#

which means that you can differentiate it by using the product rule

#color(blue)(d/dx(f(x)) = [d/dx(f(x))] * g(x) + f(x) * d/dx(g(x)))#

In your case, the derivative of

#d/dx(y) = [d/dx(x)] * (x^2 - 2)^(3/2) + x * d/dx(x^2-2)^(3/2)#

Now, to find

#d/dx(u^(3/2)) = d/(du)u^(3/2) * d/dx(u)#

#d/dx(u^(3/2)) = 3/2 * u^(1/2) * d/dx(x^2 - 2)#

#d/dx(x^2-2)^(3/2) = 3/color(red)(cancel(color(black)(2))) * (x^2 - 2)^(1/2) * color(red)(cancel(color(black)(2)))x#

Plug this back into your target derivative to get

#y^' = 1 * (x^2-2)^(3/2) + x * [3x * (x^2 -2 )^(1/2)]#

This is equivalent to

#y^' = (x^2 - 2)^(1/2) * ( x^2 -2 + 3x^2)#

#y^' = (x^2 -2 )^(1/2) * (4x^2 - 2)#

If you want, you can write this as

#y^' = color(green)(2 * (2x^2 - 1) * (x^2 -2 )^(1/2))#